ІМПЛІЦИТНО-ПРАГМАТИЧНІ ЗНАЧЕННЯ РЕСПОНСИВНИХ РЕПЛІК У СУЧАСНОМУ АНГЛОМОВНОМУ ПОБУТОВОМУ ДИСКУРСІ - Солощук, Людмила Василівна; Устименко, С.Є. (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
The article deals with the analysis of an addressee’s responsive statements with implicit meanings in modern English every day dialogical discourse. It is discovered that the primary purpose of the evasion of an addressee’s direct negative response to an addresser’s question is categoricity softening of а negative answer. Verbal and non-verbal means of expressing implicit meanings in modern English every day dialogical discourse are analyzed.